1996
DOI: 10.1523/jneurosci.16-24-08041.1996
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Inputs to ON Parasol Ganglion Cells in the Primate Retina

Abstract: In primates, the retinal ganglion cells that project to the magnocellular layers of the lateral geniculate nucleus have distinctive responses to light, and one of these has been identified morphologically as the parasol ganglion cell. To investigate their synaptic connections, we injected parasol cells with Neurobiotin in lightly fixed baboon retinas. The five ON-center cells we analyzed by electron microscopy received approximately 20% of their input from bipolar cells. The major synaptic input to parasol cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
126
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(146 citation statements)
references
References 73 publications
19
126
1
Order By: Relevance
“…This might seem surprising in light of the correlation between mammalian ganglion cell types that show strong gain control and those that receive a large degree of amacrine cell input (Shapley and Victor, 1978;Freed and Sterling, 1988;Benardete et al, 1992;Kolb and Nelson, 1993;Weber and Stanford, 1994;Jacoby et al, 1996Jacoby et al, , 2000. Our results are consistent, however, with studies in salamander, which showed that gain control in ganglion cells can be explained primarily by gain control in presynaptic bipolar cells (Kim and Rieke, 2001;Rieke, 2001).…”
Section: Discussionsupporting
confidence: 47%
“…This might seem surprising in light of the correlation between mammalian ganglion cell types that show strong gain control and those that receive a large degree of amacrine cell input (Shapley and Victor, 1978;Freed and Sterling, 1988;Benardete et al, 1992;Kolb and Nelson, 1993;Weber and Stanford, 1994;Jacoby et al, 1996Jacoby et al, , 2000. Our results are consistent, however, with studies in salamander, which showed that gain control in ganglion cells can be explained primarily by gain control in presynaptic bipolar cells (Kim and Rieke, 2001;Rieke, 2001).…”
Section: Discussionsupporting
confidence: 47%
“…Together with our findings indicating that WNT7B was localized to retinal ganglion cells and that its expression was significantly upregulated in experimental myopic eyes, these data support the hypothesis that WNT7B and GJD2 co-operatively regulate the normal growth of the eye through interactions between the alpha-ganglion cells and AII amacrine cells. Interestingly, alpha-ganglion cells are predominantly observed in the peripheral retina and have large dendritic regions to receive inputs from amacrine cells 47,[53][54][55][56][57] . The hypothesis that alpha- ganglion cells and AII amacrine cells are implicated in emmetropization is consistent with the peripheral defocus theory, a theory of myopia development that has been supported by clinical evidence [58][59][60][61] .…”
Section: Discussionmentioning
confidence: 99%
“…At this eccentricity (ϳ2 mm below the streak), all cells with mean diameters Ͻ8 m are amacrine cells on the basis of signatures. Brace, 1992;Penn et al, 1994;Jacoby et al, 1996;Stafford and Dacey, 1997;Xin and Bloomfield, 1997). Most amacrine cells are GABA immunoreactive, and GABA-immunoreactive dendrites comprise ϳ80% of the mass of the inner plexiform layer (Marc, 1992(Marc, , 1999bMarc et al, 1995Marc et al, , 1998.…”
Section: Coupling Signaturesmentioning
confidence: 99%